2014
DOI: 10.1212/wnl.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac dysfunction after aneurysmal subarachnoid hemorrhage

Abstract: WMAs are independent risk factors for clinical outcome after aSAH. This relation is partly explained by a higher risk of DCI. Further study should aim at treatment strategies for these aSAH-related cardiac abnormalities to improve clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 36 publications
3
65
1
Order By: Relevance
“…As reported previously for patients with subarachnoid hemorrhage [21], elevation of troponin I levels may, on the one hand, result from intraventricular blood and, therefore, meningeal irritation, leading to strong systemic stress-responses [22,23]. As a result, an enhanced release of catecholamines and consequently higher myocardial stress may reflect a neurocardiac dysbalance, evident also after ICH, notably in those patients with intraventricular involvement [21,22,24]. In addition, up to now, the longitudinal occurrence of troponin elevations in ICH patients was only insufficiently established and pathophysiological considerations further include an increase of intracranial pressure additionally triggering sympathetic storms [10,21,[24][25][26].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…As reported previously for patients with subarachnoid hemorrhage [21], elevation of troponin I levels may, on the one hand, result from intraventricular blood and, therefore, meningeal irritation, leading to strong systemic stress-responses [22,23]. As a result, an enhanced release of catecholamines and consequently higher myocardial stress may reflect a neurocardiac dysbalance, evident also after ICH, notably in those patients with intraventricular involvement [21,22,24]. In addition, up to now, the longitudinal occurrence of troponin elevations in ICH patients was only insufficiently established and pathophysiological considerations further include an increase of intracranial pressure additionally triggering sympathetic storms [10,21,[24][25][26].…”
Section: Discussionmentioning
confidence: 56%
“…Assessment of serial troponin I levels during hospital stay revealed a further increase in the rate of elevated troponin levels, a finding predominantly driven by increased ventricular involvement. As reported previously for patients with subarachnoid hemorrhage [21], elevation of troponin I levels may, on the one hand, result from intraventricular blood and, therefore, meningeal irritation, leading to strong systemic stress-responses [22,23]. As a result, an enhanced release of catecholamines and consequently higher myocardial stress may reflect a neurocardiac dysbalance, evident also after ICH, notably in those patients with intraventricular involvement [21,22,24].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Until now, authors have extrapolated from data in the cardiologic literature in an attempt to set a threshold for normal GLS values in ICU ventilated patients. In a large Norwegian multi-centric nation-wide study [27], the authors studied 1,266 healthy subjects. Although global longitudinal strain increases with age (implying strain impairment), the overall normal global longitudinal strain was -17.4%.…”
Section: Systolic Function Assessed With Ste In Patients Undergoinmentioning
confidence: 99%
“…Previous studies have shown that development of NCM predicts poor neurological outcome [1,11]. However, much less is known about these patients' cardiac outcomes, and if cardiac dysfunction persists and further complicates neurological recovery.…”
Section: Introductionmentioning
confidence: 99%